Representative democracy: 1958-1998, in contemporary venezuelan liberal thought: Critical Assessment - Ruiz Chataing, David (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
We address the optics on the social, political and economic regime emerged after 1958 until its collapse in 1998. We synthesize their strong criticism of the economic policies of the democratic governments. They denounced the lousy administration of enormous resources, the corruption, the inefficiency and the waste. Along with the acknowledgment that despite its flaws, there was a political democracy, the need for reforms is pointed out as a way to increase representation, citizen control, decentralization, and the full validity of the Rule of Law, market economy and individual responsibility.